2014
DOI: 10.1016/j.buildenv.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

A data-mining approach to discover patterns of window opening and closing behavior in offices

Abstract: Understanding the relationship between occupant behaviors and building energy consumption is one of the most effective ways to bridge the gap between predicted and actual energy consumption in buildings. However effective methodologies to remove the impact of other variables on building energy consumption and isolate the leverage of the human factor precisely are still poorly investigated. Moreover, the effectiveness of statistical and data mining approaches in finding meaningful correlations in data is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 228 publications
(119 citation statements)
references
References 34 publications
8
111
0
Order By: Relevance
“…Studies which model the occupants' interaction with buildings and control systems have included lighting controls (Reinhart et al 2006), shading devices (Haldi and Robinson 2010) and ventilation (Yun et al 2008). Other studies have focused on occupancy presence, fundamental for occupancy research as most occupant behaviour patterns are influenced by occupancy (Roetzel et al 2010;D'Oca and Hong 2014;Zhao et al 2014;Feng et al 2015). Characterising the stochastic nature *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Studies which model the occupants' interaction with buildings and control systems have included lighting controls (Reinhart et al 2006), shading devices (Haldi and Robinson 2010) and ventilation (Yun et al 2008). Other studies have focused on occupancy presence, fundamental for occupancy research as most occupant behaviour patterns are influenced by occupancy (Roetzel et al 2010;D'Oca and Hong 2014;Zhao et al 2014;Feng et al 2015). Characterising the stochastic nature *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, it has been successfully applied in economics, retails, telecommunication, and financial services [4]. Recently, efforts have also been made to investigate the application of data mining in HVAC field, including building energy consumption prediction [5,6], building energy management [7,8], fault detection and diagnosis [9,10], and occupant behaviour [11,12].…”
Section: Technical Approachmentioning
confidence: 99%
“…Field-measured data and large-scale surveys confirmed that these window opening behaviors, which are represented as probabilistic models (logit or Weibull functions), have been adopted by several BPS programs to determine when occupants open windows [32] [33]. Occupant behavior stochastic models are data driven and improve modeling assumptions of occupant activities in the BPS programs [34] [35][36] [37].…”
Section: Introductionmentioning
confidence: 99%